The Role of Income Distribution in the Diffusion of Corporate Social Responsibility1. (5th November 2014) - D'Alessandro, Simone; Fanelli, Domenico
Abstract The purpose of this paper is to investigate the link between corporate social responsibility (CSR) growth and income distribution. We present a general equilibrium model where social responsibility enters both firms' and consumers' decisions. At equilibrium, different degrees of CSR diffusion may arise. We study the conditions under which there exists a virtuous circle which ties increases in the diffusion of CSR to reductions in income inequality. Under certain circumstances, any policy which promotes CSR diffusion induces a reduction in income inequality. By contrast, when such conditions are not satisfied, only redistributive policies may generate the virtuous circle.